Facilitating disabled athletes’ English learning through an intensive English-speaking coaching program - Nur Arifah Drajati; Fadilah Umar; Febriani Fajar Ekawati; Ma'rifatul Ilmi; Hilda Rakerda (Jadila: Journal of Development and Innovation in Language and Literature Education, 2023)
Increased communication possibilities and access to vital social capital make English proficiency crucial in sports and the larger society. As a result, athletes must be proficient in speaking English to expand their communication opportunities, particularly disabled athletes. In response, this case study explored the implementation of an English-speaking coaching program for disabled athletes in Indonesia, focusing on its impact on facilitating their speaking skills. It explored the nuanced experiences and perspectives of disabled athletes participating in the program, shedding light on the effectiveness of tailored language coaching in improving their communication abilities. The study employed in-depth interviews and participant observations to capture the lived experiences of disabled athletes engaged in the coaching program. Fifteen national disabled para-cycling athletes participated in this study. We designed the coaching program to accommodate their needs, incorporating interactive sessions, role-playing scenarios, and real-life communication simulations. We identified four themes in this study: increased confidence, enriched vocabularies, enhanced professional opportunities, and improved English proficiency. The results indicated that the tailored coaching program positively facilitated the disabled athletes’ English-speaking skills. Through rich narrative accounts, athletes expressed increased confidence in using English, a more remarkable ability to communicate effectively with coaches and peers, and a heightened sense of empowerment. This study further concludes that English-speaking skills for athletes with special needs matter and that language coaching program needs to be further organized to support athletes’ language skills.